Analisis Gender Terhadap Hukum Keluarga Islam Indonesia (Studi Terhadap Hak-hak Wanita Pasca Cerai) - Azni, Azni (Asy-Syirah: Jurnal Ilmu Syariah dan Hukum, 2015)
Indonesia as a modern Muslim state, through its Islamic family law, has greatly sought the indiscrimination against women, especially in the context of the law and its implementation. This study aims to determine number of womens rights after divorce which has been formulated in Indonesian Islamic family law. The library research by using content analysis approach obtainsthe findings of the research are the rights acquired by women after divorce which are in Indonesian Islamic family law such as; mutah, livelihood, refuse of reconciliation, hadlanah and joint property rights, are no gender bias and are not found any elements of marginalization, subordination, double work load, negative labeling and violence against women in Islamic family law in Indonesia.